2020
DOI: 10.1177/0033294120934705
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Value Orientation, Game Context and Trust on Cooperative Behavior After Cooperative Video Game Play

Abstract: This study explores the effects of the cooperative video game context, social value orientation (SVO) and trust on cooperative behavior. The main finding is that collaborative game play significantly increases cooperative behavior, especially in prosocial individuals. In addition, a mediation model is established in which trust partially mediates the association between the game mode and cooperative behavior. The results indicate that playing collaborative games increases cooperation in prosocial people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Trust is important for the establishment and maintenance of social relationships between people [19]. As Bosma suggests, the positive influence of collaboration instead of punishment [20].…”
Section: Trust Promoting Cooperative Behaviormentioning
confidence: 99%
“…Trust is important for the establishment and maintenance of social relationships between people [19]. As Bosma suggests, the positive influence of collaboration instead of punishment [20].…”
Section: Trust Promoting Cooperative Behaviormentioning
confidence: 99%
“…Penelitian yang dilakukan oleh [6] dimana peserta bermain game Overcooked bersama. Hasil dari riset tersebut menunjukkan bahwa komponen Cooperative pada game kontribusi kepada kepercayaan dan sikap kooperatif yang berakhir dalam sikap kooperatif yang lebih positif setelah main bersama.…”
Section: Penelitian Yang Pernah Dilakukan Seperti Dari Jurnal the Inf...unclassified
“…Social relationship studies have indicated that trust plays a crucial role in understanding each partner's willingness and developing collaborative behavior (Wang et al, 2022;Zheng et al, 2021), particularly in virtual interpersonal interactions. Therefore, an individual's high confidence level is present when partners are willing to collaborate with others or offer relevant feedback in a PBL group/team.…”
Section: Hypothesis Developmentmentioning
confidence: 99%